The smart wife why Siri, Alexa, and other smart home devices need a feminist reboot - Strengers, Yolande 1981-; Kennedy, Jenny (The MIT Press, 2020)
"A fascinating look at the gendering of smart homes, how they came to be so, and how modern households can and should be domains of equality"--